Pelatihan Pembukuan Sederhana pada Usaha Warung dengan Memanfaatkan Aplikasi Buku Warung di Desa Marga Bhakti Kecamatan Sinar Peninjauan Kabupaten OKU - Refki Renaldi; Darman Safe'i; Gitta Destalya Adrian Nova; Yulitiawati Yulitiawati; Hasiatul Aini (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
This training aims to serve the community to provide an understanding to grocery store entrepreneurs about the importance of recording or bookkeeping of their activities and business progress, and to introduce the BukuWarung application to grocery store entrepreneurs in Marga Bakti Village. The problem found was their lack of knowledge and understanding of accounting, especially recording and bookkeeping to the preparation of financial reports. Their previous understanding that recording and bookkeeping were difficult, troublesome, and time-consuming became an obstacle to learning accounting. In the era of IT-based technology and the Internet of Things (IoT), the use of BukuWarung-based technology that can be accessed anywhere has become a basic human need. The BukuWarung-based bookkeeping application can be used as a tool for recording the flow of money in and out that can be used easily and applicatively for business actors, both small and medium.